A contatto con l’incognito: conversazione su jazz e improvvisazione - Cappelletti, Arrigo; Sandrini, Furio (Scenari, 2021)
The ability to lead us beyond our limits, into the unknown, is a key aspect of jazz improvisation. Hence the accompanying feeling of happiness. However, for this to occur the players of this dialogue must put aside their ego and quest for personal success. It is only by leaving aside our ego and finding our “us” again, that jazz can find its feminine side, the result of a continuous attention towards the other and, at the same time, the naturalness and spontaneity of playing. By rediscovering this impossible naturalness, jazz improvisation draws closer to its true purpose, that is to do away with censorship, and reveals its real essence, a never-ending discourse, all inconclusive, not enclosed within a code, and inspires a true revolution in education and in teaching.